Petawatt and exawatt class lasers worldwide. (2019) - Danson, Colin N.; Haefner, Constantin; Bromage, Jake; Butcher, Thomas; Chanteloup, Jean-Christophe F.; Chowdhury, Enam A.; Galvanauskas, Almantas; Gizzi, Leonida A.; Hein, Joachim; Hillier, David I.; Hopps, Nicholas W.; Kato, Yoshiaki; et al.
Abstract : In the 2015 review paper 'Petawatt Class Lasers Worldwide' a comprehensive overview of the current status of high-power facilities of ${>}200~\text{TW}$ was presented. This was largely based on facility specifications, with some description of their uses, for instance in fundamental ultra-high-intensity interactions, secondary source generation, and inertial confinement fusion (ICF). With the 2018 Nobel Prize in Physics being awarded to Professors Donna Strickland and Gerard Mourou for the development of the technique of chirped pulse amplification (CPA), which made these lasers possible, we celebrate by providing a comprehensive update of the current status of ultra-high-power lasers and demonstrate how the technology has developed. We are now in the era of multi-petawatt facilities coming online, with 100 PW lasers being proposed and even under construction. In addition to this there is a pull towards development of industrial and multi-disciplinary applications, which demands much higher repetition rates, delivering high-average powers with higher efficiencies and the use of alternative wavelengths: mid-IR facilities. So apart from a comprehensive update of the current global status, we want to look at what technologies are to be deployed to get to these new regimes, and some of the critical issues facing their development.